Antibodies against angiotensin II receptor type 1 and endothelin A receptor are increased in COVID-19 patients - Miedema, Jelle R.; Janssen, Matthijs L.; Thüsen, Jan von der; Endeman, Henrik; Langerak, Anton W.; Hellemons, Merel E.; van Nood, Els; Peeters, Bas W. A.; Baart, Sara J.; Schreurs, Marco W. J. (Frontiers in Immunology, 2023)
Background Increased titers of autoantibodies targeting the G-protein-coupled receptors angiotensin II type 1 receptor (AT1R) and endotelin-1 type A receptor (ETAR) are associated with severe coronavirus disease 2019 (COVID-19) infection. The aim of this study was to determine whether 1) these antibodies are specifically related to COVID-19 disease pathogenesis or increased during any severe respiratory illness, 2) if they are formed during illness, and 3) if they correlate with inflammatory markers or long-term symptoms. Methods Antibodies against AT1R, ETAR, and antinuclear antibodies (ANAs) were measured in n=40 prospectively enrolled COVID-19 patients and n=207 COVID-19 patients included in a biobank. Clinical and laboratory findings were prospectively and retrospectively assessed in both cohorts, and results were combined for analysis. The presence of auto-antibodies against AT1R or ETAR in peripheral blood was compared between hospitalized patients with COVID-19 and controls (n=39). Additionally, AT1R and ETAR titers were compared between patients with an unfavorable disease course, defined as intensive care admission and/or death during hospital admission (n=121), to those with a favorable disease course (n=126). A subset of intubated patients with severe COVID-19 were compared to intubated patients with acute respiratory distress syndrome (ARDS) due to any other cause. Results Significantly increased AT1R and ETAR antibody titers were found in COVID-19 patients compared to controls, while titers were equal between favorable and unfavorable COVID-19 disease course groups. On ICU, intubated patients with COVID-19 had significantly increased AT1R and ETAR titers compared to patients with ARDS due to any other cause. The titers did not correlate with baseline inflammatory markers during admission or with diffusion capacity, cognitive impairment, or fatigue measured at 3 months follow-up. Conclusions In patients hospitalized for COVID-19, antibodies against AT1R and ETAR are increased compared to controls and patients with ARDS due to other causes than COVID-19. The baseline antibody titers do not correlate with inflammatory markers or long-term symptoms in this study.